The Effect of Financial Literacy on Household Interest in Utilizing Insurance Financial Products - Novitasari, Kadek Ayu Santhi; Setyari, Ni Putu Wiwin (Jurnal Ekonomi Kuantitatif Terapan; Vol 18 No 1 (2025): Vol. 18, No. 1, FEBRUARI 2025 (pp.1-149)DO - 10.24843/JEKT.2025.v18.i01.P08, 2025)
Insurance is needed to provide financial protection. However, Household trust in insurance financial products and services is lower than in banking, especially in Bali Province. Financial literacy is needed to increase trust in insurance financial services. This research aims to examine the condition of financial literacy at the household level in Bali Province and analyze the influence of financial literacy on household interest in utilizing insurance financial service products in Bali Province. This research used a quantitative associative approach with survey data collection techniques using questionnaires. The data analysis technique for this research uses the formation of index numbers to measure the financial literacy index at the household level in Bali Province and Binary Logistic Regression to determine the influence of the independent and dependent variables. The analysis results show that the financial literacy index in Bali province is in the high category, and financial literacy has a significant relationship with household interest in utilizing insurance financial services.